Embodied Design Cognition: Action-Based Formalizations in Architectural Design. (December 2014) - Smithwick, Daniel; Sass, Larry
This paper frames design knowledge as formalizable physical actions that can more fully exploit future design tools and production methods. As computational design tools become more physically interactive and integrated into our environment we need new research frameworks to develop theories of physical design action as a form of knowledge. Symbolic theories of design knowledge traditionally frame design activity as a mental process and as a result researchers have not fully explored the potential for bodily-based computational design knowledge. We present an action-based design notation drawing inspiration from music performance theory to illustrate how this may impact design research. We discuss findings from situated cognition in cognitive science as an alternative framework for exploring and expanding design knowledge. We conclude with suggestions for future work in robotic-aided design cognition.